2014
DOI: 10.1128/jvi.02106-14
|View full text |Cite
|
Sign up to set email alerts
|

Gammaherpesvirus Latency Differentially Impacts the Generation of Primary versus Secondary Memory CD8+T Cells during Subsequent Infection

Abstract: Unlike laboratory animals, humans are infected with multiple pathogens, including the highly prevalent herpesviruses. The purpose of these studies was to determine the effect of gammaherpesvirus latency on T cell number and differentiation during subsequent heterologous viral infections. Mice were first infected with murine gammaherpesvirus 68 (MHV68), a model of EpsteinBarr virus (EBV) infection, and then after latency was established, they were challenged with the Armstrong strain of lymphocytic choriomening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Possible mechanisms include chronic stimulation of innate immune responses that regulate adaptive immunity, antigenic mimicry, cross-reactive immune responses, altered antigen presentation and changes in differentiation of memory and naïve lymphocyte responses (Hensley et al, 2007; Oldstone, 2005; Selin et al, 2006; Stelekati et al, 2014; Stelekati and Wherry, 2012; Virgin, 2014; Virgin et al, 2009). Latent infection with the γ-herpesvirus used in our studies, MHV68, alters the number and phenotype of memory CD8+ T cells (Barton et al, 2014). Latent MCMV infection also results in profound alteration in the T cell compartment, leading to impaired naïve T cell function (Cicin-Sain et al, 2012), despite no increase in susceptibility to secondary challenge with influenza virus, West Nile virus, or vesicular stomatitis (Marandu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms include chronic stimulation of innate immune responses that regulate adaptive immunity, antigenic mimicry, cross-reactive immune responses, altered antigen presentation and changes in differentiation of memory and naïve lymphocyte responses (Hensley et al, 2007; Oldstone, 2005; Selin et al, 2006; Stelekati et al, 2014; Stelekati and Wherry, 2012; Virgin, 2014; Virgin et al, 2009). Latent infection with the γ-herpesvirus used in our studies, MHV68, alters the number and phenotype of memory CD8+ T cells (Barton et al, 2014). Latent MCMV infection also results in profound alteration in the T cell compartment, leading to impaired naïve T cell function (Cicin-Sain et al, 2012), despite no increase in susceptibility to secondary challenge with influenza virus, West Nile virus, or vesicular stomatitis (Marandu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the mechanism was shown to involve persistent activation of the innate immune system (42). Such effects were either not studied in aging (40,44) or were found to not affect immune responses in older adults (43).…”
Section: Discussionmentioning
confidence: 99%
“…Mice infected with γMHV-68 (an EBV-like virus) or murine CMV show heterologous protection against subsequent bacterial infection [**47], although this effect appears to be transient, and has been attributed to higher proinflammatory cytokines in the host [48]. A similar approach has shown that γMHV-68+ mice subsequently infected with LCMV have impaired DC maturation, and altered T cell priming to skew the population toward memory rather than effector subsets [49]. In mouse models, infection with γMHV-68 exacerbates EAE (a model of Multiple Sclerosis) [50].…”
Section: Aging With Persistent Herpesvirus Infections and The Speciamentioning
confidence: 99%